THE EFFECT OF SERVICE QUALITY ON CUSTOMER SATISFACTION IN CV. PANGEAN JAYA ABADI IN KUANTAN SINGINGI DISTRICT - Teguh Hendra (Sean Institute, 2022)
Competition in the economic field both national, regional and multinational is getting intense. Trade wars occur between nations trying to dominate the market. The concept of marketing is having thoughts so that how marketing activities can be carried out based on a solid philosophy, which uses responsive and responsible marketing. In general, the purpose of this study is to determine the effect of service quality on satisfaction. The number of samples in this study were 37 people. From the results of the overall validity test of statement items between the service quality variable and the satisfaction variable, it was declared valid because the value of rcount> rtable (0.3246) was obtained. The results of simple linear regression obtained a value of Y = 11.410 + 0.719X. From the results of the partial test or t test, it is obtained that the value of tcount (6.148) > the value of ttable (2.03011) with a significant level of 0.000 <0.05 means that the service quality variable has a significant effect on the satisfaction variable. And the coefficient of determination R2 is 0.519 or 51.9% while the rest (100 – 51.9 = 48.1) or 48.1% is influenced by other variables that are ignored or not selected in this study.